Contesting higher education student movements against neoliberal universities - Della Porta, Donatella 1956-; Cini, Lorenzo; Guzmán Concha, César (Bristol University Press, 2020)
This close investigation of student protests in the UK, Canada, Chile and Italy represents the first comparative review of the subject. Setting the wave of demonstrations within the contexts of student activism, social issues and political movements, it casts new light on their impact on higher education and on the broader society
Keywords: Geschichte; Studentenbewegung; Höheres Bildungswesen; Neoliberalismus; Bildungspolitik; Großbritannien; Italien; Kanada; Chile; Student movements / Cross-cultural studies; Student movements; Cross-cultural studies